"On the Same Page, but in Different Books?" Exploring Pedagogical Beliefs of Various Stakeholders in Management Education - Poulose, Jeanne; Sharma, Vinod (Prabandhan: Indian Journal of Management, 2019)
The declining MBA enrolment numbers and campus placements are indicators of an alarming situation in India. The key stakeholders comprising of teachers, students, and corporates desire the same outcome, which is students with high employability. This implies everyone is on the same page, but the falling salary packages and rising unemployment make one wonder if this page is from a different book for each stakeholder? Through this study, we tried to bring in more clarity on the perception of the stakeholders in such B-schools regarding their choice of pedagogy to be employed. Drawing on the body of literature and peer group discussions, this study identified 15 pedagogical methods employed in higher education. Thus, to explore the preferred pedagogy, an exploratory research was designed and owing to the categorical nature of the data collected over a seven-month period, correspondence analysis was applied. Data analysis confirmed the existence of a huge perceptual gap amongst the stakeholders about the appropriate pedagogy to be used in management education. Student engagement and application based learning emerged as the two most important dimensions of pedagogy in this study. The results and findings can be extended further to understand causes for this perceptual gap and identify measures to bridge the same to ensure that these B-schools yield job ready students resulting in MBA regaining its lost glory.